Can the comparison of above- and below-ground litter decomposition improve our understanding of bacterial and fungal successions?. (May 2019) - Sauvadet, Marie; Fanin, Nicolas; Chauvat, Matthieu; Bertrand, Isabelle
Abstract: The relationship between litter quality and life strategy of soil microorganisms (copiotrophy vs oligotrophy) is important for understanding soil processes such as decomposition. Yet, whether and how this relationship may vary with the addition of substrates of contrasting quality (i.e., labile vs recalcitrant) has rarely been evaluated for both bacteria and fungi simultaneously. Using a 3-month incubation experiment with either maize leaves (enriched in soluble carbon (C)) or roots (enriched in structural C), we measured changes in litter quality in association with the composition of bacterial and fungal communities assessed via pyrosequencing after 0, 15, 35 and 91 days. Overall, leaf addition led to a higher differentiation from the unamended soil for bacterial and early-decomposers fungal communities compared with root addition. This finding clearly indicates that the differentiation of microbial communities strongly depends on substrate quality for both bacterial and fungal communities. Further, the differentiation of bacterial communities after litter addition remained relatively similar throughout the incubation period. This suggests that many bacterial taxa are more adapted to complex C compounds than previously thought. Finally, our study underscores the limits of the copiotroph–oligotroph model at the phylum level and the necessity to work at a finer taxonomic resolution. Highlights: Compared with root addition, leaf addition results in higher differentiation of microorganisms. Litter quality impacts on the differentiation of early-decomposers fungi and bacteria. Bacterial taxa are adapted to complex carbon compounds. Most phyla are constituted by both copiotrophic and oligotrophic genera.